Pressure-Volume Relationships in the Spinal Canal and Potential Neurological Complications After Epidural Fluid Injections - Bosscher, Hemmo (Frontiers in Pain Research, 2022)
High-volume fluid injections into the spinal canal may lead to severe neurological complications. But when anatomical or pathological conditions in the spinal canal are unfavorable, even small volume epidural injections can cause dangerously high epidural, subarachnoid, and intracranial pressures or pressure gradients. Data obtained from the scientific literature and direct clinical observation are used to derive a first-order approximation of epidural, subarachnoid, and intracranial pressure responses to epidural fluid injections. Maximum allowable fluid volumes for single or multiple divided fluid injections over time are calculated. In the presence of spinal pathology, 10 ml of fluids may increase epidural pressure to >100 mmHg. Injection speed >4 ml per second may also generate dangerously high intraspinal and intracranial pressures. Intermitted bolus injections provide limited protection, but intraspinal pressures may rise very fast when a critical total injected volume is reached. Potential complications of increased intracranial pressures or large pressure waves include nerve palsies, tinnitus, blindness, stroke, and death. Spinal injections or endoscopy should be performed in an awake responsive patient or with direct cerebrospinal fluid pressure monitoring. A set of guidelines for epidural fluid management is given.